The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.13181/mji.v20i2.441
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of stage IIB osteosarcoma treated by limb salvage surgery using extracorporeally irradiated (ECI) autograft

Abstract: Latar belakang: Teknik radiasi ekstrakorporeal merupakan alternatif tindakan pembedahan penyelamatan ekstremitas pada kasus osteosarkoma khususnya di pusat layanan dengan keterbatasan endoprostesis dan alograf. Penelitian ini bertujuan untuk mengevaluasi hasil tindakan pembedahan penyelamatan ekstremitas dengan otograf yang diradiasi secara ekstrakorporeal pada pasien-pasien osteosarkoma yang datang ke RSCM. Metode: Studi ini menggunakan desain kohort retrospektif yang dilakukan pada 20 pasien osteosarkoma sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Our previous study ECI demonstrated a good MSTS score (70.63%) with 20% infection rate. Local recurrence also reported as high as 20% [7]. Sharma et al [31] reported an infection rate of 14%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study ECI demonstrated a good MSTS score (70.63%) with 20% infection rate. Local recurrence also reported as high as 20% [7]. Sharma et al [31] reported an infection rate of 14%.…”
Section: Discussionmentioning
confidence: 99%
“…These advancements in bone tumor management have given both surgeons and patients more options for treatment, other than mere limb ablation. Currently, 90–95% of patients with sarcoma of the extremities that were administered in tertiary referral centre can undergo musculoskeletal LSS with a successful result [[5], [6], [7], [8], [9]].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parosteal osteosarcoma is a relatively rare bone tumour. It is reported that, in our national referral hospital, the incidence of osteosarcoma was 16.8 cases per year [4]. From this series, we identified six patients with parosteal osteosarcoma over a period of twenty years.…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma is known to have a bimodal age distribution with first peaked in young adults and the second in the elderly [2, 4 -7]. Within a period of 13 years (1995-2007), there were 219 cases (16.8/year) at Cipto Mangunkusumo General Hospital, Jakarta with the largest distribution in the second decade [8].…”
Section: Introductionmentioning
confidence: 99%